IMPLEMENTATION OF DIABETIC FOOT EXERCISES TO IMPROVE FOOT SENSITIVITY IN TYPE 2 DIABETIC PATIENTS - Maidatul Ustadiyah; Esti Widiani; Anggun Setyarini (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Patients with diabetes mellitus are at a higher risk of developing diabetic foot ulcers, which can occur due to decreased foot sensitivity. The decreased sensitivity is caused by elevated blood sugar levels, leading to reduced blood flow that can damage nerves in the foot area, resulting in decreased sensation in the soles of the feet, often characterized by complaints of pain in the foot area. To reduce the risk of complications in the foot area, action is needed to increase foot sensitivity, one of which is by performing diabetic foot exercise. The aim of this study is to determine the benefits of implementing diabetic foot exercise to enhance foot sensitivity in middle-aged patients with type 2 diabetes mellitus. This research is a qualitative descriptive case study with a case study approach. The results of the sensitivity examination on subject 1 before diabetic foot exercise on the right foot were 2 (moderate sensitivity) and the left foot was 1 (low sensitivity). Meanwhile, the sensitivity examination results on subject 2 were 2 (moderate sensitivity) on both feet. After performing diabetic foot exercise, the sensitivity on subject 1 was 3 (good sensitivity) on both feet, and on subject 2, it was 3 (good sensitivity) on both feet. Based on these results, there was an increase in foot sensitivity in both subjects. It is recommended that the subjects continue diabetic foot exercise independently or with family members to reduce complaints in the foot area.